Holiday and celebration bread in five minutes a day : sweet and decadent baking for every occasion - François, Zoë; Hertzberg, Jeff (St. Martin's Press, 2018)
Offers one hundred recipes for holiday breads that use homemade, high-moisture yeast dough, including such breads as lavash, braided challah, monkey bread, sufganiyot, and panettone.